"Yuk Cegah Virus Corona!" Edukasi Pencegahan Corona Melalui Buku Interaktif Anak-Anak - Putri, Alifia Ananda; Arumdani, Yeni; Fadhil Fauzi Rizal, Muhammad Fathi (CITRAWIRA : Journal of Advertising and Visual Communication, 2021)
Corona Virus or COVID-19 was first discovered in December 2019 in Wuhan, China. On January 30, 2020, WHO announced that this epidemic was a global health emergency, spreading so quickly that it reached various countries including Indonesia. Covid-19 had weakened and paralyzed various sectors in Indonesia and even all countries. One of the impacts is in the world of education. Since the implementation of the online system, there have been many pros and cons that have occurred among the community as well as challenges that must be faced with the existence of this distance learning system (PJJ). Early childhood education is undeniably affected by COVID-19. The research method uses empirical methods by collecting data sources from libraries and journals that have been there before. The results of the study concluded that the making of an interactive book "Come on, Prevent Coronavirus!" is a type of busy book in which this book can provide various activities for children so that they will not be bored in digesting the learning material.